Stigmatodon attenuatoides (Tillandsioideae, Bromeliaceae): a new mat-forming species on inselbergs of southeastern Brazil - Couto, Dayvid Rodrigues; Manhães, Vitor Da Cunha; Costa, Andrea Ferreira Da (Phytotaxa, 2020)
During the taxonomic revision of the genus Stigmatodon, we found an unknown epilithic mat-forming species, morphologically close to S. belloi, on vertical granitic surfaces on inselbergs in southern Espírito Santo state, Brazil. We described and illustrated the new species, including a comparative analysis of characters that distinguish it from similar species. We also provide data on habitat, ecology, geographical distribution and evaluation about its threat of extinction according to the criteria of the IUCN.